Mastering GitHub : advanced GitHub pages, external service integration, and the GitHub API - Porteneuve, Christophe (O'Reilly, 2016)
"In this Mastering GitHub training course, GitHub expert Christophe Porteneuve will teach you everything you need to know about advanced GitHub Pages, integrating GitHub with external services, using the GitHub API, and advanced account management--including organizations. This course is designed for users that already have a good understanding of GitHub. You will start by learning how to publish advanced websites and demos on GitHub pages. From there, Christophe will teach you how to use GitHub.com faster with keyboard shortcuts, as well as how to leverage third-party services for advanced workflow automation, such as continuous integration, code coverage monitoring, and more. This video tutorial also teaches you how to write custom integration servers and command-line tools using the GitHub API. Finally, you will learn about advanced account management, with a focus on organization management, and the nitty-gritty of billing and payments. Once you have completed this computer based training course, you will have learned everything you need to know about advanced GitHub Pages, integrating GitHub with external services, and the GitHub API."--Resource description page.